LIGETI’S “STRING QUARTET No.1”; STYLISTIC INCONGRUENCE? - ŢIPLEA TEMEŞ, Bianca (Studia Universitatis Babes-Bolyai Musica, 2008)
Compared to Ligeti’s String Quartet no.2, Métamorphoses nocturnes is a piece that has been less explored, although it towers over the author’s early creations. Using a sole melodic motif extracted from Bartók’s piano piece Klänge der Nacht, the Quartet develops a set of syntactic and language characteristics that confer this Budapest period work a reverential gesture to Ligeti’s outstanding predecessor. The arch form structure, the continuous variation technique, the fusion between chromaticism and diatonicism, they all highlight a compelling interconnection with Bartók’s universe. Our emphasis on the stylistic incongruence concept emerges from the contrast between the five constitutive sections of the arch form and the coda segment. Whilst the constant transformation technique of the generative motif in all five sections polarizes titles such as Musica Ricercata, Sechs Bagatellen für Bläserquintett, the coda conceals a stylistic border zone and prefaces an irreversible evolution process towards significant works of the next decade – Glissandi, Apparitions, Athmosphères. It leads directly to the meta-language of sonorous fields and static blocks projected beyond any gravitational space, where musical parameters dissolve in a unique one: the timbre colour. In the coda segment, Ligeti operates a complete suspension of the temporal dimension and induces a sonorous entropy. These new elements will trigger in future works the structural collapse and the disintegration of the articulated form, which will become noteworthy stilemas of his later creation. The title’s declared metamorphosis required a multi-level semantic decoding, but the analysis finally provided all the arguments in order to consider String Quartet no.1 synonymous with Ligeti’s definitive stylistic conversion.